Design of an achromatic wide-view circular polarizer using normal dispersion films. Issue 1 (2nd January 2019) - Oh, Seung-Won; Kim, Sang-Hyeok; Baek, Jong-Min; Yoon, Tae-Hoon
ABSTRACT: Proposed herein is an achromatic wide-view circular polarizer (CP) using normal dispersion films, which can suppress the light reflection over all the polar and azimuth angles. For normal incidence, the proposed CP with +A/−A/+C plates shows almost zero light reflection over all the wavelengths. For oblique incidence, the maximum reflected light of the proposed CP with +A/−A/+C plates is approximately 68 times lower than that of a CP with a single quarter-wave plate. Moreover, because all the films that were used had normal wavelength dispersion, they could be easily fabricated at a relatively low manufacturing cost.